Influence of Precursor Mixtures on the Laser Chemical Vapor Deposition of TiC Fibers - Kendall J. Mitchell; Gregory B. Thompson (Fibers, 2024)
In this study, the hyperbaric (2 bar) laser chemical vapor deposition of TiC fibers grown under various percent pressures of hydrogen and ratios of ethylene and titanium tetrachloride (2:1 or 1:1) are reported. In the hydrogen-rich (85%) condition, sequential fiber depositions became stunted as a result of a loss of hydrogen, which served as a reducing agent for the metal halide as hydrogen evolved with the hydrocarbon gas in the reaction zone because of the Le Chatelier principle. For the hydrogen-lean (25%) condition, the intrinsic fiber growth rate was invariant, but gas phase nucleation resulted in the hydrocarbon forming carbon soot in the chamber which subsequently deposited and coated on the fibers. In the hydrogen-balanced composition (50%), the 2:1 precursor ratio resulted in inconsistent intrinsic growth rates which ranged from approximately 30 μm/s to 44 μm/s. However, for the hydrogen-balanced (50%) 1:1 condition, the intrinsic growth rate variation was reduced to approximately 12 μm/s. The differences in fiber uniformity, composition, and structure under these process conditions are discussed in terms of hydrogen’s ability to serve as a reducing agent, a fluid to transport heat from the deposition zone, and alter the structure of the fiber through thermophoresis.